Hybrid synchronous motor magnetic field research; Seventh Japanese-Mediterranean and Central European Workshop on Applied Electromagnetic Engineering for Magnetic, Superconducting and Nano Materials. (JAPMED'7), 6-9 July 2011, Budapest, Hungary, Danubius Hotel Gellert - Suvorkova Е. Е. Elena Evgenyevna (2011, 2011)
Title screen